Perancangan Naskah Video Animasi 2d 'Jaga Alam, Cegah Kepunahan' dengan Struktur Naratif Tiga Babak melalui Perspektif Surili - Ganiyah Rahma (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2026)
This project is motivated by the increasing rate of deforestation in Indonesia, which has led to ecosystem degradation and the threat of extinction for endemic species, as well as the relatively low environmental awareness among young people due to the abstract and systematic presentation of data. The main objective of this work is to produce a 5-minute 2D animation that effectively raises awareness among adolescents aged 14–24 about the threat of environmental extinction caused by deforestation in Indonesia. This is achieved through a three-act narrative approach using a first-person perspective of the Javan surili, positioned as a narrative “lens” and a representation of a victim of a damaged ecosystem, allowing abstract issues to be understood in a more personal, emotional, and empathetic way. The method includes pre-production (research, concept development, and scriptwriting), production (development of dialogue, monologue, and visual direction based on a three-act structure), and post-production (narrative evaluation and script refinement). The result is an educational animation script titled “Jaga Alam, Cegah Kepunahan,” which integrates scientific data, visual storytelling techniques, and multimedia learning principles to deliver messages in an informative and emotional manner. The three-act structure successfully constructs a systematic storyline from introduction, conflict, to resolution with a call to action. The conclusion shows that 2D animation with a personal narrative approach is effective in transforming environmental issues into accessible messages, increasing empathy, and encouraging audience awareness and participation in environmental conservation.